Left and right populists in Spain: from origins to COVID pandemics - A. L. Dunaev (Ибероамериканские тетради)
After Franco’s death in 1975, a transition to democracy took place in Spain, accompanied by formation of a two-party system. While the overall transition was peaceful, it did not solve a number of important problems in Spanish society that became of paramount importance over the past decade. The peculiarities of the regime enshrined in the 1978 Constitution, combined with the consequences of the financial and economic crisis of 2008-2010, created the breeding ground in which populist parties formed in 2010s. The article examines the crisis of the post-Francoist political model as a prerequisite for emergence of populist parties, particularities of their programs, as well as the actions taken by them in the context of the Coronavirus pandemic. The author notes that by 2014 there developed a situation when the main parties of the country either demonstrated an unwillingness to solve pressing problems or proposed solutions that were unacceptable for a significant part of the population. In such a situation, social protest began to take its political form. The emergence of populists in the electoral field has largely renewed the country’s political agenda, revitalizing discussions on topical issues and forcing a change with the ‘heavyweights’ of Spanish politics – the Socialists and the People’s Party. The author concludes that transformation of political discourse can lead to a renewal of an entire political system of the country and a search for some new solutions to issues that remain key on the political agenda of Spain over the past decades.